Social Media as Art Education Distance Learning Systems Platform in Indonesia - Agus Tatang Sopandi; Pamela Mikaresti; Ana Nurmalia; Nia Erlina (International Journal of Pedagogy and Teacher Education, 2025)
Innovations in utilizing advances in science, knowledge, and technology need to achieve this goal optimally by utilizing social media as a learning resource. This study investigates social media as a learning resource in Art Education course in Elementary School as mandatory courses for advances in science, knowledge, and technology needed to achieve this goal optimally. This research method uses quantitative descriptive, namely creating audio-visual learning media for synchronous and asynchronous learning for elementary school-aged children uploaded to social media, and then identified the application using SWOT analysis. Respondents in this study were 312 students of the Elementary School Teachers program in arts education courses in Indonesia. SWOT analysis shows the meeting point of the IFAS tangent is obtained. This means the development of the media has good strengths and opportunities rather than weaknesses and threats. The strategy obtained from the matrix is aggressive, namely a strategy by optimizing internal strengths and opportunities. Social media shows a positive response as a medium for learning. The development of digital learning media shows promise, paving the way for innovation in all art education materials. Utilizing social media enhances teaching and learning processes, making material comprehension easier and aiding in achieving learning objectives.  The teaching and learning process experiences novelty by utilizing social media to present material that is easy to understand so that learning objectives can be achieved.